2010
DOI: 10.1111/j.1755-3768.2009.01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab for the treatment of choroidal neovascularization secondary to angioid streaks: one year of follow-up

Abstract: ABSTRACT.Purpose: To evaluate the efficacy and safety of intravitreal bevacizumab at one year follow-up, for the treatment of choroidal neovascularization (CNV) associated with angioid streaks. Methods: A retrospective case series of eighteen eyes of 17 patients with CNV secondary to angioid streaks treated with intravitreal bevacizumab between October 2006 and May 2008. Ophthalmic evaluation including best corrected visual acuity (BCVA), slit lamp biomicroscopic examination, optical coherence tomography (OCT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
0
14
1
Order By: Relevance
“…Similar results after a longer follow-up were reported by Martinez-Serrano et al [45] in 14 eyes. In contrast, our data disagree with the data obtained by Sawa et al [31] , Finger et al [34] , El Matri et al [35] , Mimoun et al [24] , Ladas et al [37] , and Shah et al [40] , who demonstrated a trend for improvement or stability of functional and anatomical outcomes in their case series. In the study by Ladas et al [37] , eyes were treated according to a treatand-extend protocol, showing beneficial results with a mean of 7.1 injections over a 16-month period.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Similar results after a longer follow-up were reported by Martinez-Serrano et al [45] in 14 eyes. In contrast, our data disagree with the data obtained by Sawa et al [31] , Finger et al [34] , El Matri et al [35] , Mimoun et al [24] , Ladas et al [37] , and Shah et al [40] , who demonstrated a trend for improvement or stability of functional and anatomical outcomes in their case series. In the study by Ladas et al [37] , eyes were treated according to a treatand-extend protocol, showing beneficial results with a mean of 7.1 injections over a 16-month period.…”
Section: Discussioncontrasting
confidence: 56%
“…We think that a treat-and-extend protocol may allow better visual and anatomical results, but it imposes a higher burden of intravitreal treatments on patients. Explaining these differences in results is difficult, but we think that the different selection criteria for cases (naïve/not naïve, extra/juxta/subfoveal CNV), different durations of follow-up, and different treatment regimens used (PRN protocol [24,31,34,35,40,45] , single injection followed by a PRN protocol [41] , and treat-and-extend protocol [37] ) certainly played an important role. In fact, our results show a strong tendency towards relapse and confirm the difficulties in controlling a disease that deteriorates in the long term despite a close follow-up, especially in the case of subfoveal CNV and in eyes with a low baseline visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…2 The recent advent of treatment based on intravitreal anti-VEGF has completely revolutionized the management of AS-related CNV, both for subfoveal and nonsubfoveal forms, generally providing positive functional outcomes. [3][4][5][6][7][8][9][10][11][12] Nevertheless, all the clinical studies turned out to be largely uneven with regard to treatment duration of follow-up, treatment regimen, and lesion monitoring. For these reasons, the identification of a biomarker related to the activity of the CNV would certainly simplify the management of CNV treatment over a long-term follow-up.…”
mentioning
confidence: 99%
“…In keeping with data previously reported [10,20,[31][32], visual outcomes following PDT were poor; the two patients that received PDT in the current study had vision of CF at the 12 month follow-up visit. Given that visual results following laser and PDT are often disappointing [19][20], anti-VEGF therapies would appear to be the treatment of choice at present time for AS-associated CNV [27,[33][34][35][36][37][38][39][40]. Table 1 summarises currently available studies (presenting > five cases) on the use of anti-VEGF in patients with AS-associated CNV.…”
Section: Discussionmentioning
confidence: 99%